The Effect of Product Quality, Price and Promotion on the Purchase Decision of Indihome Services Pt. Telkom Indonesia (Study on Indihome Consumers in Semarang City Area) (International Journal of Scientific Research and Management (IJSRM), 2023)
The background of this research is based on the decrease in the number of Indihome service users in 2021 in the city of Semarang and the differences in the results of previous studies. This study aims to analyze the effect of product quality, price and promotion on purchasing decisions of Indihome PT. Telkom Indonesia Semarang City Area.The data used is primary data, with data collection techniques through questionnaires. The population used is all customers who buy IndiHome services in 2021 in Semarang City, with a total research sample of 100 respondents, with a sampling technique using simple random sampling. The data analysis technique used multiple linear regression analysisThe results obtained that partially product quality has a positive and significant effect on purchasing decisions with a significance value of 0.000 <0.05. Price has a positive and significant effect on purchasing decisions with a significance value of 0.00 < 0.05, and promotion has a positive and significant effect on purchasing decisions with a significance value of 0.002 < 0.000. The results simultaneously obtained that product quality, price, and promotion together have a positive and significant effect on purchasing decisions with a significance value of 0.000 <0.05. The results of the coefficient of determination obtained a value of 0.744, meaning that product quality, price, and promotion can explain variations in purchasing decisions of 74.4%.